New genera and species of Ripipterygidae (Orthoptera, Tridactyloidea) from mid-Cretaceous Kachin amber - Ole-Kristian Odin Schall; Chengquan Cao; Martin Husemann (Contributions to Entomology)
Two new genera and species of Ripipterygidae Ander, 1939 are described from mid-Cretaceous Kachin amber of Northern Myanmar. Ozymandipteryx campana gen. et sp. nov. is remarkable for its absent or very reduced metatarsus. In modern species of Tridactyloidea, a reduced metatarsus can only be found in the Tridactylidae Brullé, 1835 genera Ellipes Scudder, 1902 and Xya Latreille, 1809, but not in Ripipterygidae. Magnidactylus robustus Xu et al., 2020, type species of the genus, is found to share the character of a fully reduced metatarsus (apical spurs were previously misinterpreted as metatarsus), but M. robustus differs from O. campana in several important characters and hence remains a separate genus. However, a new genus Yakkhapipteryx is erected to include the other two former Magnidactylus species M. mirus Gu et al., 2022 (Yakkhapipteryx mirus comb. nov.) and M. gracilis Gu et al., 2022 (Yakkhapipteryx gracilis comb. nov.), which both have a metatarsus in normal condition. Another newly described taxon is Ciconipteryx bidactylus gen. et sp. nov. This species is the first fossil Ripipterygidae with only two dactyls on its protibia, a feature it shares with the modern species Mirhipipteryx pulicaria (Saussure, 1896). Ciconipteryx bidactylus stands out due to its long mid- and hindlegs in relation to its body size. This character may have enabled it to perform very efficient jumps. The new species add to the diversity of Ripipterygidae from Kachin amber, expanding our knowledge of this little studied family and raising new possibilities for interpreting their evolutionary history.